Carbohydrate mouth rinse failed to reduce central fatigue, lower perceived exertion, and improve performance during incremental exercise - Pires, Flávio O.; Pinheiro, Fabiano A.; Brietzke, Cayque; Franco-Alvarenga, Paulo Estevão; Veras, Katherine; de Matos, Eugênia C. T.; Rodacki, André L. F.; Ugrinowitsch, Carlos (Frontiers in Nutrition, 2024)
We examined if carbohydrate (CHO) mouth rinse may reduce central fatigue and perceived exertion, thus improving maximal incremental test (MIT) performance. Nine recreational cyclists warmed up for 6 min before rinsing a carbohydrate (CHO) or placebo (PLA) solution in their mouth for 10 s in a double-blind, counterbalanced manner. Thereafter, they performed the MIT (25 W·min−1 increases until exhaustion) while cardiopulmonary and ratings of perceived exertion (RPE) responses were obtained. Pre- to post-MIT alterations in voluntary activation (VA) and peak twitch torque (Tw) were determined. Time-to-exhaustion (p = 0.24), peak power output (PPO; p = 0.45), and V̇O2MAX (p = 0.60) were comparable between conditions. Neither treatment main effect nor time–treatment interaction effect were observed in the first and second ventilatory threshold when expressed as absolute or relative V̇O2 (p = 0.78 and p = 0.96, respectively) and power output (p = 0.28 and p = 0.45, respectively) values, although with moderate-to-large effect sizes. RPE increased similarly throughout the tests and was comparable at the ventilatory thresholds (p = 0.56). Despite the time main effect revealing an MIT-induced central and peripheral fatigue as indicated by the reduced VA and Tw, CHO mouth rinse was ineffective in attenuating both fatigues. Hence, rinsing the mouth with CHO was ineffective in reducing central fatigue, lowering RPE, and improving MIT performance expressed as PPO and time-to-exhaustion. However, moderate-to-large effect sizes in power output values at VT1 and VT2 may suggest some beneficial CHO mouth rinse effects on these MIT outcomes.